Land Law - RIDDAL, J.G (LexisNexis UK, 2003)
This text provides a clear description of the development of the English system of land tenure, estates in land and other basic principles of land law, and is recommended reading for students of law. This edition has been updated in light of the Land Registration Act 2000 and new rules relating to commonhold